2021
DOI: 10.1021/acs.langmuir.1c00885
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-Elastic Effect in Non-Newtonian Ferrofluid Droplets Impacting Superhydrophobic Surfaces

Abstract: In this article, we propose, with the aid of detailed experiments and scaling analysis, the existence of magneto-elastic effects in the impact hydrodynamics of non-Newtonian ferrofluid droplets on superhydrophobic surfaces in the presence of a magnetic field. The effects of magnetic Bond number (Bo m), Weber number (We), polymer concentration, and magnetic nanoparticle (Fe3O4) concentration in the ferrofluids were investigated. In comparison to Newtonian ferrofluid droplets, addition of polymers caused rebound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…A height-alterable droplet dispenser coupled with a digitized controller unit has been used to generate and release the droplets from different heights. As similar to our previous studies, , we have performed experiments at different Weber numbers ( ), i.e., the ratio of inertial forces to surface tension forces, and Ohnesorge numbers ( ) i.e., the ratio of viscous forces to both inertial and capillary forces, where ρ, U , D o , and σ represent the density, impact velocity, preimpact droplet diameter, and surface tension of the fluid, respectively. The Reynolds number is denoted as Re in the definition of the Ohnesorge number.…”
Section: Methodsmentioning
confidence: 95%
“…A height-alterable droplet dispenser coupled with a digitized controller unit has been used to generate and release the droplets from different heights. As similar to our previous studies, , we have performed experiments at different Weber numbers ( ), i.e., the ratio of inertial forces to surface tension forces, and Ohnesorge numbers ( ) i.e., the ratio of viscous forces to both inertial and capillary forces, where ρ, U , D o , and σ represent the density, impact velocity, preimpact droplet diameter, and surface tension of the fluid, respectively. The Reynolds number is denoted as Re in the definition of the Ohnesorge number.…”
Section: Methodsmentioning
confidence: 95%
“…Ferrofluid has demonstrated a wide range of studies, including encapsulation, mixing, droplet manipulation, evaporation, and cell sorting . The impact dynamics of magnetic droplets on a nonmagnetic substrate is widely studied in the literature, which involves the effect of magnetic field on the dynamics of droplet spreading and postimpact self-assembly. In this regard, Shyam et al have studied the impact dynamics of a water-based ferrofluid on PDMS substrate. It is found that upon impact, the ferrofluid droplet undergoes Rosensweig instability and exhibits several regimes of equilibrium configurations .…”
Section: Introductionmentioning
confidence: 99%
“…The impact hydrodynamics of liquid droplets, Newtonian fluids or otherwise, on different surfaces in the presence of external electric or magnetic fields [1] has great importance in many applications, such as inkjet printing [2], ferrohydrodynamic three-dimensional inkjet printing [3], magnetic drug targeting in microfluidic applications [4], spray painting, spray cooling [5], controlling the liquid metal droplet deposition during welding or soldering [6], electrohydrodynamic (EHD) droplet-on-demand inkjet printing [7], electro spraying [8,9], electrowetting [10] electrohydrodynamic jet (E-jet) [11] printing and so forth.…”
Section: Introductionmentioning
confidence: 99%